2017
DOI: 10.1159/000480086
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular, Biological, and Immunological Agents Inducing Hypophysitis

Abstract: b 251 HAF and VA Hospital, Athens , Greece thus its true prevalence is probably underestimated. The pathophysiology of hypophysitis induced by anticancer agents is not fully clarified. In most cases, treatment requires dose adjustment of the offending drug and pituitary hormone replacement. This mini-review aims to present currently available information regarding hypophysitis related to new molecular, biological, and immunological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 84 publications
0
22
0
1
Order By: Relevance
“…Recent studies in mouse and human pituitary glands have revealed that anti-CTLA-4 hypophysitis is characterized by the presence of circulating anti-pituitary antibodies and lymphocytic infiltration of the gland [43]. Ectopic expression of CTLA-4 has also been observed in the normal hypophysis in mice, particularly in prolactin- and TSH-secreting cells [43], as well as in hypophysitis and adenomas of the human pituitary gland [17, 44] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in mouse and human pituitary glands have revealed that anti-CTLA-4 hypophysitis is characterized by the presence of circulating anti-pituitary antibodies and lymphocytic infiltration of the gland [43]. Ectopic expression of CTLA-4 has also been observed in the normal hypophysis in mice, particularly in prolactin- and TSH-secreting cells [43], as well as in hypophysitis and adenomas of the human pituitary gland [17, 44] (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…b A monoclonal antibody against PD-1 can block this pathway and result in upregulation of immune response and inhibition of tumor growth. Figure reproduced with permission of S. Karger AG, Basel from the original source [44].…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Other factors affecting the reported incidence of ipilimumab-induced hypophysitis are the lack of a precise and consistent definition of hypophysitis in different studies and the duration of follow-up that ranged from few months up to several years (Table 1). 16,20 Compared to patients who receive ipilimumab, those who receive treatment with anti-PD-1 or anti-PD-L1 agents are significantly less likely to develop hypophysitis. In a metaanalysis of 34 studies, it has been reported that the incidence of hypophysitis was 0.4% with anti-PD-1 and <0.1% with anti-PD-L1 therapy.…”
Section: Prevalence and Epidemiology Of Ipilimumab-induced Hypophysitismentioning
confidence: 99%
“…Recent in vitro and in vivo studies have suggested that immune and genetic factors are implicated and a combination of inflammatory and immune mechanisms result to tissue damage. 16,36,37 CTLA-4 acts as a negative regulator of the B7 and CD28 co-stimulation axis. In an immune response, activated T-cells upregulate the expression and the translocation of CTLA-4 in the plasma membrane.…”
Section: Pathophysiologymentioning
confidence: 99%
“…As for the underlying pathophysiology of ICP inhibitor-induced hypophysitis, it has been postulated that pituitary immunogenicity is mediated by CTLA-4 antigen expression by pituitary endocrine cells. This leads to complement activation and infiltration of macrophages (type II hypersensitivity reaction) and autoreactive T lymphocytes (type IV hypersensitivity reaction) (28,29,30,31). The susceptibility of pituitary cells to ICP inhibitors has been recently nicely demonstrated in a patient with pituitary carcinoma resistant to all available treatments including temozolomide but responding robustly to combination ICP inhibitor therapy (32).…”
Section: Autoimmune Hypophysitis Related To Immune Checkpoint (Icp) Imentioning
confidence: 99%